2021
DOI: 10.1186/s12876-021-01854-x
|View full text |Cite
|
Sign up to set email alerts
|

Successful use of montelukast in eosinophilic gastroenteritis: a case report and a literature review

Abstract: Background Eosinophilic gastrointestinal disorders, also known as eosinophilic gastroenteritis, are rare inflammatory conditions characterized by eosinophilic infiltration of different parts of the gastrointestinal tract, along with peripheral eosinophilia in most cases. Other known causes for gut eosinophilic infiltration must be excluded to confirm the diagnosis of eosinophilic gastroenteritis. Symptoms of the disorder depend on the affected gastrointestinal tract segment and depth of involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
0
9
0
1
Order By: Relevance
“…Fundamentally, the treatment strategy for secondary EGIDs is to treat the primary disease; however, it was difficult to improve the digestive symptoms using only nutritional therapy in our case. Several studies have reported montelukast sodium as an effective treatment for EGIDs [11,12]. Montelukast is a selective and competitive of the cysteinyl leukotriene receptor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fundamentally, the treatment strategy for secondary EGIDs is to treat the primary disease; however, it was difficult to improve the digestive symptoms using only nutritional therapy in our case. Several studies have reported montelukast sodium as an effective treatment for EGIDs [11,12]. Montelukast is a selective and competitive of the cysteinyl leukotriene receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Montelukast sodium has become the focus of attention in the treatment of EGIDs. One study described the successful use of montelukast as a steroid-sparing agent in 63% adults patients [11], however its effectiveness as a treatment for EGIDs in children remains to be evaluated. In our case, sufficient effectiveness was not observed.…”
Section: Discussionmentioning
confidence: 99%
“…If prednisone cannot be tolerated due to side effects, budesonide remains a viable alternative as it has a lower systemic side effect profile [ 1 ]. Other agents like azathioprine, cromolyn sodium, ketotifen, montelukast, and biologics like mepolizumab have been explored as adjuncts for the refractory disease but cannot be firmly recommended as first-line therapies due to conflicting data and lack of large-scale studies [ 1 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of montelukast, a leukotriene receptor antagonist, for EGIDs with duodenal lesions was shown in a double-blind, randomized, placebo-controlled crossover study (Friesen et al 2004). In addition, there are several case reports in which montelukast monotherapy was effective as a first line treatment (Neustrom and Friesen 1999;El-Alali et al 2021). Montelukast is a medication associated with few adverse events and may be considered for use before corticosteroids, especially in cases with duodenal lesions.…”
Section: Discussionmentioning
confidence: 99%